Safety and outcomes of percutaneous tracheostomy in coronavirus disease 2019 pneumonitis patients requiring prolonged mechanical ventilation. Issue 11 (4th November 2020) - Takhar, A; Tornari, C; Amin, N; Wyncoll, D; Tricklebank, S; Arora, A; Ahmad, I; Simo, R; Surda, P
Abstract: Objectives: Tracheostomy for coronavirus disease 2019 pneumonitis patients requiring prolonged invasive mechanical ventilation remains a matter of debate. This study analysed the timing and outcomes of percutaneous tracheostomy, and reports our experience of a dedicated ENT–anaesthetics department led tracheostomy team. Method: A prospective single-centre observational study was conducted of patients undergoing tracheostomy, who had been diagnosed with coronavirus disease 2019 pneumonitis, between 21st March and 20th May 2020. Results: Eighty-one patients underwent tracheostomy after a median (interquartile range) of 16 (13–20) days of invasive mechanical ventilation. Median follow-up duration was 32 (23–40) days. Of patients, 86.7 per cent were successfully liberated from invasive mechanical ventilation in a median (interquartile range) of 12 (7–16) days. Moreover, 68.7 per cent were subsequently discharged from hospital. On univariate analysis, there was no difference in outcomes between early (before day 14) and late (day 14 or later) tracheostomy. The mortality rate was 8.6 per cent and no deaths were tracheostomy related. Conclusion: Outcomes appear favourable when patients are carefully selected. Percutaneous tracheostomy performed via a multidisciplinary approach, with appropriate training, was safe and optimised healthcare resource utilisation.